Areas of economic activity of the population of the hillfort of Polyuty in the Inva river basin in the middle ages - Vostroknutov, A.V. (Perm Federal Research Centre Journal, 2018)
The article presents the results of the application of cartographic methods of investigation for the area surrounding the hillfort of Polyuty (X-XIII centuries a.d.). It concludes that taking into account the soil analysis, the relief and labor expenditures it is possible to identify arable lands, hayfields and pastures on this territory.